Juridical Study of Notary on Forgery of Deed of Division of Joint Property in Criminal Cases - Rahmawati, Dina; Abdullah, Ali (Golden Ratio of Law and Social Policy Review, 2025)
The forgery of authentic deeds carried out by notary office employees has profound implications for the resulting deeds' evidentiary strength and legal enforceability. This study aims to analyze the applicability and evidentiary strength of the deed of division of common property forged by notary employees and evaluate legal responsibility in the juridical context of the notary. The approach used is normative juridical with a qualitative analysis method through literature studies and case studies of the Palembang District Court Decision Number 996/Pid.B/2020/PN. PLG. The results of the study show that although formally the forged deed has not been legally canceled by the court, materially the deed has lost its force as an authentic deed and is only valuable as a deed under hand. This reinforces the importance of the principle of prudence and supervision by notaries on the performance of their employees. These findings contribute to clarifying the boundaries of notary legal responsibility and strengthening legal protection for the community that uses notary services.